PENGEMBANGAN MULTIMEDIA INTERAKTIF POWTOON PADA MATA PELAJARAN EKONOMI POKOK BAHASAN KEBIJAKAN MONETER UNTUK SISWA KELAS XI IPS DI SMA NEGERI 1 SINGOSARI - Marta Dwi Pangestu; Achmad Ali Wafa (Jurnal Pendidikan Ekonomi, 2018)
Media have an important role in channeling information from teachers to learners. The development and utilization of ICT-based learning media both offline and online can be utilized by educators. In practice, however, teachers use less of learning media during the learning process. The method often used by teachers is lecture, which causes students to feel bored in following the lesson so that the understanding of the material is less good. By using appropriate learning media in the learning process will make students more active. Development of interactive multimedia PowToon aims to develop and produce a medium of learning in the form of interactive multimedia on the subject of economics subject of monetary policy as well as see and test the effectiveness of interactive multimedia design. This development model uses a development model from Borg and Gall that has been modified as needed. The type of data in this study uses quantitative data and qualitative data. Validation of product contents is done by using a questionnaire with scale scale based on Likert scale. Validation test results show that this medium is "valid and usable" with average percentage of material expert 1 of 95%, material expert 2 is 81,67%, media expert is 93,24%, and field trial is 90,15 %. Based on the results of expert validation and field trials it can be concluded that PowToon interactive multimedia products are valid and suitable for use as a medium of learning in school. DOI: https://dx.doi.org/10.17977/UM014v11i12018p071